Information Culture in Intercultural Space. Moderation of Values - Sylwia Jaskuła (Ksiegarnia Akademicka Publishing, 2021)
The current role of information culture is combined with the change of the role of information in modern media civilization. This gives rise to new educational needs, including multicultural education, with relevant education in the field of information competence as its important element. In the new space of presence of a man, which is formed as a result of the interaction of real and virtual resources, these competences become more intercultural. At the same time, the diversity of cultures in space and their variability in time results in a lack of uniformity in the interpretation, perception and analysis of information, which leads to difficulty in defining a uniform model of culture and information competency. In this reality one of the main challenges facing today’s cultures becomes keeping up with the changes of the information society and the dynamics of contemporary information culture which are generated, exceeding the barriers of stability, sustainability and predictability.